Didáctica de las lenguas extranjeras: los enfoques comunicativos. - Díaz-corralejo Conde, Joaquín (Didáctica. Lengua y Literatura, 1996)
Checkup and situation of communicative approches proposals and objectives, as a methodology that is looking for an answer to the main problems of foreign languages learning and teaching. A critical point of view, from practice, of the essential notions and of the differen¡ scientific subjects that give explanatory clements.